Pengaruh nilai pelanggan dan pengalaman pelanggan terhadap kepuasan konsumen Telkomsel - Ellena Nurfazria Handayani; Octavia Dwi Putri (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study was conducted with the aim of knowing the effect of experience value (X1) and customer experience (X2) on Telkomsel's consumer satisfaction (Y). This study uses a quantitative method. The number of respondents is 100 respondents who are people who have bought and used products at Telkomsel at least 3 times in the last 3 months and are in the North Bekasi area. The analytical tool used is multiple linear regression. The results of this study show the value of the F test with an Fcount of 194.094 (Fcount > Ftable, 194.094 > 3.09) and the coefficient of determination (R2) of 0.800 or 80%, which means that the variable customer value and overall/simultaneous customer experience have influence on customer satisfaction.